Chemical balance - Cook, Ernest Mansel (My University, 1900)
Introduction: The balance is an instrument by means of which we ascertain the mass of bodies in grains, grams, or any other units of mass. We have many mechanical contrivances by the use of which we determine the heavier of two bodies, or the ratio of their weights, among which we mention the following as being the most extensively and approximately successfully employed: spring balances, chain balances, lever balances, torsion balance, and hydrostatic weighing machine. We will concern ourselves only with the lever balance, which, throughout this discussion, will be designated by the term balance. The balance of primitive days consisted simply of a straight beam, supported at the middle and flattened at the ends upon which were placed the objects to be weighed. Subsequently scale pans were attached and, finally, an enterprising tradesman conceived the notion of using in one pan an object or set of objects as a counterpoise. From this idea has developed our “set of weights.” The weights first used were common objects, such as rocks and pebbles of a convenient size. We still retain the name “stone” (28 pounds) in one of our old English systems of weights.
Citation: Cook, Ernest Mansel. Chemical balance. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Chemistry; Balance; Weights; Measures; Theses